The Asian financial crisis lessons for a resilient Asia - Woo, Wing Thye; Sachs, Jeffrey; Schwab, Klaus (MIT Press, 2000)
This book analyzes the Asian financial crisis of 1997-1999. In addition to the issues of financial system restructuring, export-led recovery, crony capitalism, and competitiveness in Asian manufacturing, it examines six key Asian economies-China, Indonesia, Japan, Korea, Malaysia, and Thailand. The book makes clear that there is little particularly Asian about the Asian financial crisis. The generic character of the crisis became clear during 1998, when it reached Russia, South Africa, and Brazil. The spread of the crisis reflects the rapid arrival of global capitalism in a world economy not used to the integration of the advanced and developing countries.